Perancangan Sistem Informasi Transparansi Dana Desa Berbasis Website di Desa PandanLandung - Araujo, Julio Abilio; Nurdewanto, Bambang (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
Pandanlandung Village's financial administration is still done by hand, which impedes information openness and public engagement. For this reason, this project intends to develop and construct a web-based village fund transparency information infrastructure. The created system shows financial transactions, budgetary allocations, income statistics, project progress, and a community ambition element to increase the responsibility of the village administration. Data was gathered via observations, interviews, and literature reviews, and the research used a waterfall development model using the research and development approach. This methodology ensured a structured and systematic development process, beginning with requirements definition and culminating in implementation. To ensure that every feature operates as intended by the user, system testing used black box approaches. The input, storage, data presentation, and authentication elements all performed effectively, according to the findings. The successful execution of black box testing on all major modules confirms the system's reliability and user-friendliness, ensuring it meets functional requirements. By putting this system in place, the administration of village funds becomes more transparent, citizens can get information more easily, and other villages may adopt it as a model for digitalizing public financial governance.